Promovisanje ruralnog turizma putem društvenih mreža i digitalnog preduzetništva: Uvidi od operatera domaćinstava za smeštaj u Sikimu - Lepcha, Sonam Dorjee; Bhutia, Dr. Jigmie Wanchuk; Bhutia, Dr. Ruth Marie (Turizam, 2026)
In today’s digital age, social media can transform small rural businesses into globally visible enterprises. This study explored the adoption, perceived opportunities, and challenges of social media use among rural homestay operators in Sikkim, India. A qualitative research design was employed, and semi-structured interviews were conducted with 30 homestay operators across all districts of Sikkim and analyzed using thematic analysis. The findings revealed that social media adoption was highly strategic and uneven, with WhatsApp, Facebook, and Instagram being the most frequently used platforms by the participants. Operators strategically use WhatsApp, Facebook, and Instagram to promote homestays, build trust, and engage with guests, with video content being the most effective medium. However, adoption is limited by infrastructural constraints, digital skill gaps, operational time pressures, and exposure to online risks. This study contributes to the understanding of digital entrepreneurship in rural tourism and offers practical guidance for improving social media adoption by small-scale operators. The findings also provide policymakers with evidence to design targeted interventions for infrastructure development and capacity-building programs.